Use of Phraseologisms in the Poetry of I. Yusupov - Sadykova, Raya (Research Parks Publishing LLC, 2022)
The article analyzes the phraseologisms in the poetry of I. Yusupov on the types of stylistic use and individual author's phraseologisms.